Everolimus-Based Therapy versus Chemotherapy among Patients with HR+/HER2− Metastatic Breast Cancer: Comparative Effectiveness from a Chart Review Study - Nanxin Li; Yanni Hao; Jipan Xie; Peggy L. Lin; Valerie Koo; Erika Ohashi; Eric Q. Wu (International Journal of Breast Cancer)
Objective. To compare the real-world effectiveness of everolimus-based therapy and chemotherapy in postmenopausal women with hormone-receptor-positive/human-epidermal-growth-factor-receptor-2-negative (HR+/HER2−) metastatic breast cancer (mBC). Methods. This retrospective chart review examined a nationwide sample of postmenopausal HR+/HER2− mBC women in community-based oncology practices. Patients received everolimus-based therapy or chemotherapy for mBC between 07/01/2012 and 04/15/2013, after failure of a non-steroidal aromatase inhibitor. Overall survival (OS), progression-free survival (PFS), and time on treatment (TOT) were compared using Kaplan-Meier analysis and Cox proportional hazards models adjusting for line of therapy and baseline characteristics. Results. 234 and 137 patients received everolimus-based therapy and chemotherapy. Patients treated with everolimus-based therapy tended to have less aggressive mBC than patients treated with chemotherapy. Multivariate-adjusted Cox models showed that everolimus-based therapy was associated with significantly longer OS [hazard ratio (HR) = 0.37, 95% confidence interval (CI): 0.22–0.63], PFS (HR = 0.70, 95% CI = 0.50–0.97), and TOT (HR = 0.34, 95% CI: 0.25–0.45) than chemotherapy. Adjusted comparative effectiveness results were generally consistent across lines of therapy. Conclusion. In this retrospective chart review of postmenopausal HR+/HER2− mBC patients, treatment with everolimus-based therapy was associated with longer OS, PFS, and TOT than chemotherapy.